2015
DOI: 10.1021/acs.inorgchem.5b00448
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Precursors for Deposition: Synthesis, Structure, and Thermal Studies of Cyclopentadienylcopper(I) Isocyanide Complexes

Abstract: We report here the synthesis and characterization of a family of copper(I) metal precursors based around cyclopentadienyl and isocyanide ligands. The molecular structures of several cyclopentadienylcopper(I) isocyanide complexes have been unambiguously determined by single-crystal X-ray diffraction analysis. Thermogravimetric analysis of the complexes highlighted the isopropyl isocyanide complex [(η(5)-C5H5)Cu(CN(i)Pr)] (2a) and the tert-butyl isocyanide complex [(η(5)-C5H5)Cu(CN(t)Bu)] (2b) as possible copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…The IR spectrum of this compound showed, in addition to intense oxalate C=O stretching bands at 1622 and 1602 cm -1 , a pair of bands in the N-H/O-H stretching region at 3430 and 3192 cm -1 . Interestingly, the crystal structure of this blue compound revealed that it was not simply the copper(II) dppds complex, as might have been expected, but a smaller copper(II) di-(2-picolyl)amine oxalate complex (12), entirely devoid of sulfur, as shown in Figure 13. In the solid-state structure of complex 12, each copper center is  3 -coordinated by one molecule of di-(2-picolyl)amine,  2 -coordinated by one planar oxalate anion, and  1 -coordinated by a second oxalate ion (in the same plane as the first), which is in turn  2 -coordinated to a neighboring copper center.…”
Section: Complex With Mixed Nxsy Ligandmentioning
confidence: 68%
See 2 more Smart Citations
“…The IR spectrum of this compound showed, in addition to intense oxalate C=O stretching bands at 1622 and 1602 cm -1 , a pair of bands in the N-H/O-H stretching region at 3430 and 3192 cm -1 . Interestingly, the crystal structure of this blue compound revealed that it was not simply the copper(II) dppds complex, as might have been expected, but a smaller copper(II) di-(2-picolyl)amine oxalate complex (12), entirely devoid of sulfur, as shown in Figure 13. In the solid-state structure of complex 12, each copper center is  3 -coordinated by one molecule of di-(2-picolyl)amine,  2 -coordinated by one planar oxalate anion, and  1 -coordinated by a second oxalate ion (in the same plane as the first), which is in turn  2 -coordinated to a neighboring copper center.…”
Section: Complex With Mixed Nxsy Ligandmentioning
confidence: 68%
“…Cu(di-(2-picolyl)amine)C2O4•H2O (12) An attempt was made to isolate the copper(I) oxalate complex with the mixed NxSy ligand dppds by allowing Cu2O to react with oxalic acid in ethanol in the presence of the ligand. This complex is of interest in bioinorganic chemistry [36,37].…”
Section: Complex With Mixed Nxsy Ligandmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously investigated the relationship between alkyl group functionalization of the cyclopentadienyl ligand and both volatility and stability in copper cyclopentadienide isocyanate complexes . If we compare the temperatures at which the onset of volatilization is observed for the 10 compounds for which both the cyclopentadienyl and methyl cyclopentadienyl complex was synthesized, the general trend appears to be that the addition of a methyl substituent onto the {Cp} fragment results in a lowering of the temperature at which mass loss begins [ 1 (73 °C): 7 (62 °C); 2 (73 °C): 8 (64 °C); 4 (92 °C): 9 (86 °C); 6 (119 °C): 11 (77 °C)].…”
Section: Resultsmentioning
confidence: 99%
“…Current progress in the synthesis of (RNC)Cu I compounds allows the classification of the reported species to the following types, viz. homoleptic species [Cu(CNR) n ] + (n = 3 and 4) [29,30] and mixed-ligand complexes bearing, apart isocyanide ligand(s), different C- [31][32][33], N- [34][35][36][37], X-(X = halogen) [38] and other donor ligands [39,40]. To the best of our knowledge, no theoretical studies focused on elucidation of ligand properties and activation of RNC species by copper(I) centers are known.…”
Section: Introductionmentioning
confidence: 99%